Enhancing Ecological Validity: Virtual Reality Assessment of Executive Functioning in Children and Adolescents with ADHD - Dulce Romero-Ayuso; Antonio del Pino-González; Antonio Torres-Jiménez; Jorge Juan-González; Francisco Javier Celdrán; María Constanza Franchella; Nuria Ortega-López; José Matías Triviño-Juárez; Ana Garach-Gómez; Luisa Arrabal-Fernández; Inmaculada Medina-Martínez; Pascual González (MDPI AG, 2024)
Background: SmartAction-VR uses virtual reality to simulate daily life tasks and assess cognitive performance based on the multi-errand paradigm. This study explored whether this new task could provide insights into the executive functioning of children and adolescents with ADHD in their everyday activities. Methods: A cross-sectional study was conducted between November 2021 and December 2022. It consisted of one session and was divided into two parts (cognitive tests; and SmartAction-VR). The sample comprised 76 children and adolescents with a median age (IQR) of 13 (11-14) years and an age range of 9-17 years. Of these participants, 60.50% (n = 46) were males. Out of this sample, 40 participants were in the ADHD group and 36 were in the neurotypical group. The following instruments were used: Waisman Activities of Daily Living Scale, Assessment of Sensory Processing and Executive Functioning, Pediatric Simulator Disease Questionnaire, Digit span subtest, Stroop test, NEPSY-II Subtest of Auditory Attention and Cognitive Flexibility, Trail Making Test, Zoo Map Test, and SmartAction-VR. Results: The ADHD group demonstrated lower accuracy (U = 406, p = 0.010), higher values for total errors (U = 292, p = 0.001), more commissions (U = 417, p = 0.003), new actions (U = 470, p = 0.014), and forgetting actions (U = 406, p = 0.010), as well as fewer perseverations compared to the neurotypical group (U = 540.5, p = 0.029). Additionally, participants who forgot more actions were found to have lower independence in daily life (r = −0.281, p = 0.024). Conclusions: The correlations between the results of SmartAction-VR and activities of daily living, as well as cognitive tests, suggest that this new task could be useful for evaluating executive functioning in daily life.